The dual role of nuclear factor erythroid 2-related factor 2 in hepatocellular carcinoma: mechanisms, clinical relevance, and therapeutic opportunities - Houhong Wang; Shang Bian (Exploration of Drug Science, 2025)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is a pivotal regulator of cellular redox balance and detoxification, critical for maintaining hepatocyte homeostasis. However, its dysregulation has emerged as a key driver in hepatocellular carcinoma (HCC), the most prevalent form of liver cancer. This review synthesizes recent advancements (2023–2025) to elucidate Nrf2’s context-dependent dual functions: tumor suppressive roles during early carcinogenesis through oxidative stress mitigation, versus oncogenic effects in advanced stages via promoting proliferation, survival, and treatment resistance. We systematically analyze molecular mechanisms of Nrf2 activation, including Kelch-like ECH-associated protein 1 (KEAP1)-dependent/independent pathways and epigenetic regulation, supported by clinical data linking Nrf2 expression to patient prognosis. Preclinical and translational research on Nrf2-targeted therapies is evaluated, with a focus on combinatorial strategies overcoming resistance. Despite challenges in developing selective modulators, integrating multi-omics biomarkers and context-specific interventions offers promise for precision medicine in HCC.